Outcomes for bipolar patients assessed in the French expert center network: A 2‐year follow‐up observational study (FondaMental Advanced Centers of Expertise for Bipolar Disorder [FACE‐BD]). (12th September 2017) - Henry, Chantal; Godin, Ophelia; Courtet, Philippe; Azorin, Jean‐Michel; Gard, Sébastien; Bellivier, Frank; Polosan, Mircea; Kahn, Jean‐Pierre; Roux, Paul; Aubin, Valerie; Costagliola, Dominique; Leboyer, Marion; et al.
Abstract : Objective: A new health care system for patients with bipolar disorders was established in France under the auspices of Fondation FondaMental, based on thorough clinical assessment of patients and on close collaborations between expert centers and referring practitioners. We report the results of outcomes after 2 years of observational follow‐up of adult patients assessed within the network. Method: A total of 984 patients were included in the study. We compared several parameters (e.g., mood episodes and hospitalization) 1 year before inclusion and after 2 years of observational follow‐up using the patient as his or her own control. Other outcomes were compared at baseline and during follow‐up. We estimated the evolution of these parameters over a period of 2 years using mixed models for continuous parameters and a generalized estimating equation (GEE) model for categorical variables, adjusting for potential confounding factors. Results: Mean age was 42.7 (±12.5) years and 58.8% were women. The number of hospitalization days decreased by 55% when comparing 1 year before inclusion vs the follow‐up period. In addition, patients showed a clear functional improvement associated with a reduction of residual mood symptoms, diminished psychiatric comorbidities, improvement of sleep and a better adherence to treatment. Conclusions: This study demonstrates an overall improvement of patients followed for 2 years after an assessment in expert centers for bipolar disorders. This new organization based on a thorough clinical assessment and on personalized recommendations (drug treatments, psycho‐social strategies and lifestyle measures) sent to health care professionals, and actively involving patients and families, improves the prognosis of BD patients.